A Qualitative Study of Work Stress, Work Ethics, and Work Discipline on Employee Performance at PT. BRI Insurance MRO Jember - mohammad bayu prayoga; Sindy Agustin; Rangga Yuda Bagus Wicaksono; Pongky Arie Wijaya (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2026)
Human resources are a crucial factor in determining organizational success, particularly in the highly competitive insurance industry. Employee performance is influenced by several factors, including work stress, work ethic, and work discipline. This study aims to analyze the influence of work stress, work ethic, and work discipline on employee performance at BRI Insurance MRO Jember. This research uses a qualitative approach with a case study design. Data were collected through in-depth interviews, non-participant observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that work stress arises from high workloads, strict targets, and simultaneous tasks, leading to pressure and work fatigue. Employees’ work ethic is generally good, reflected in responsibility, professionalism, adherence to SOPs, and strong teamwork. Work discipline is also well implemented through punctuality, compliance with working hours, and timely task completion. These three factors are interrelated in influencing employee performance, where work stress tends to reduce performance, while work ethic and work discipline enhance effectiveness and work quality.